METHOD, DEVICE, SYSTEM OF MODEL-DRIVEN ENGINEERING OF EFFICIENT INDUSTRIAL AUTOMATION PROCESS AND BUSINESS PROCESS MODELING WITH BPMN USING NATIVE COMPUTATION OF XML SCHEMAS AND OBJECTS - Binder Arkadiusz (2017)
Disclosed are a method, device and/or system of a model-driven engineering of efficient industrial automation process and business process modeling with BPMN using native computation of XML schemas and objects. In one embodiment, it models a business/industrial automation process using BPMN. It creates an XML schema associated with a business object class in BPMN using XSD and natively computes the XML schema and/or an XML object using a processor and a memory. It generates an XML-transport map and dynamically creates a user interface for the XML schema. It creates the XML object with associated data resource based on the XML schema. It associates the XML object with a business object/industrial automation object. It customizes and/or processes the XML object using the user interface associated with the XML schema according to the characteristics of the business/industrial automation object.